Case report: Unusual viral evolutions following antiviral therapies in a patient with concurrent hepatitis B virus and hepatitis C virus infection - Su, Yi-Tse; Chang, Ming-Ling; Liaw, Yun-Fan (Frontiers in Medicine, 2023)
Concurrent hepatitis B virus (HBV) and hepatitis C virus (HCV) infection is not uncommon as the two viruses shared the similar transmission routes. HCV is usually the dominant virus to suppress HBV, and HBV reactivation may occur during or after the course of anti-HCV treatment. By contrast, HCV reactivation after anti-HBV therapy in the concurrent HBV- and HCV-infected patients was rarely noted. Here, we reported the unusual viral evolutions of a patient with concurrent HBV and HCV infection, in whom HCV reactivation occurred during the entecavir therapy to rescue the severe HBV flare, while the following anti-HCV combination therapy with pegylated interferon and ribavirin elicited the second HBV flare despite sustained virological response to HCV infection, and further entecavir therapy healed the flare.